(untitled) (Світ фінансів, 2017)
Затонацька Т. Г., Ткаченко О. Є. Прагматика оцінювання фіскального простору в Україні. Здійснено критичний аналіз та запропоновано індикатори й критерії оцінювання фіскального простору. З’ясовано наслідки високої частки перерозподілу ВВП через державний сектор. Надано аналітичну експрес-характеристику сучасного стану державних фінансів та удосконалено методичний підхід до вимірювання фіскального простору, що передбачає визначення інтегрального показника площини фіскального простору графічним способом. Виокремлено особливості формування фіскального простору в Україні. Затонацкая Т. Г., Ткаченко А. Е. Прагматика оценивания фискального пространства в Украине. Осуществлен критический анализ, предложены индикаторы и критерии оценки фискального пространства. Выяснены последствия высокой доли перераспределения ВВП через государственный сектор. Предоставлена аналитическая экспресс-характеристика современного состояния государственных финансов; усовершенствован методический подход к измерению фискального пространства, предусматривающий определение интегрального показателя плоскости фискального пространства графическим способом. На этой основе выделены особенности формирования фискального пространства в Украине. Zatonatska T., Tkachenko O. Pragmatics assessment of fiscal space in Ukraine. Introduction. Recently the research works and modern science foundation of public finances allowed to bring together the theoretical and practical bases to the interpretation of fiscal space. The latter represents the amount of financial resources generated by the state as a result of active fiscal political proceedings by mobilizing revenues to state and local budgets, rationalizing expenditure, etc. The purpose. The article aims to deepen methodological approaches to fiscal space measuring and its visualization using graphical methods. Results. structural and logical scheme of measuring fiscal space through the use of a graphical method of investigation are represented. Measurement of fiscal space involves the construction of petal diagram corresponding to the number of rays number of indicators of fiscal space. Thus normative values all of indicators of fiscal space marked on the diagram equals to 1. To identify dynamic changes of plane fiscal space, changes in the values of the integral index over several periods analyzed are reflected. Conclusion. Identifying problems of fiscal space forming allows to advance methodological approach of determining the integral index fiscal space by means of graphical manner using five indicators: 1) the level of GDP redistribution through the consolidated budget; 2) the ratio of expenditures of the general government to GDP; 3) the ratio of fiscal deficit to GDP; 4) the ratio of public and publicly guaranteed debt to GDP; 5) Stabilization fund assets ratio to GDP